2010
DOI: 10.4137/cin.s4774
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Selected Socio-Demographic Factors and Cancer of Oral Cavity - A Case Control Study

Abstract: Abstract:The aim of this study was to recognize factors associated with cancer of oral cavity considering socio-demographic characteristics. The cases were 350 with squamous-cell carcinoma of oral cavity diagnosed between 2005 and 2006 in Morbai, Narandia, Budharani Cancer Institute, Pune, India. Similar number of controls match for age and sex selected from the background population. Cases and controls were interviewed for tobacco related habits and general characteristics; age, gender, education and possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 14 publications
6
30
1
Order By: Relevance
“…In this present study, most of the oral cancer patients were belonging to lower class and lower middle class that is significantly correlated to OSCC (p=0.001). Our findings are consistent with to another study by (Madani et al, 2010) who reported that risk of oral cancer is inversely proportional to increasing level of education and economical status. A recent work conducted in Delhi, India by Goyal et al (2014) revealed that Majority cases were doing small business and either unemployed or labourer, more than half patients were from income less than Rs 10,000 (approximately US$ 200) per month and 10 % were from weaker section of society.…”
Section: Discussionsupporting
confidence: 93%
“…In this present study, most of the oral cancer patients were belonging to lower class and lower middle class that is significantly correlated to OSCC (p=0.001). Our findings are consistent with to another study by (Madani et al, 2010) who reported that risk of oral cancer is inversely proportional to increasing level of education and economical status. A recent work conducted in Delhi, India by Goyal et al (2014) revealed that Majority cases were doing small business and either unemployed or labourer, more than half patients were from income less than Rs 10,000 (approximately US$ 200) per month and 10 % were from weaker section of society.…”
Section: Discussionsupporting
confidence: 93%
“…A case control study from India demonstrates the presence of an association with low income. The estimated odds ratio associated with monthly household income of less than Rs 5000 was 1.7 (Madani et al, 2010a). Low SEC may be interrelated with other factors like nutrition, health care, living condition and risk behaviours contributing to the development of OC (Warnakulasuriya, 2009).…”
Section: Socioeconomic Conditions (Sec)mentioning
confidence: 96%
“…Illiterates (Balaram et al, 2002;Rajkumar et al, 2003;Subapriya et al, 2007;Muwonge et al, 2008), those who never attended school (Merchant et al, 2000) and with low educational attainment (Guneri et al, 2005) have greater risk. In the Indian population OR for OC related to education is greater for illiterates (6.4) (Subapriya et al, 2007) compared to low education level (5.3) (Madani et al, 2010a). However, another study from India failed to show low education as risk factor after controlling for age and habits (Dikshit and Kanhere, 2000).…”
Section: Socioeconomic Conditions (Sec)mentioning
confidence: 96%
See 1 more Smart Citation
“…There was a significant increase in the incidence of head and neck cancer including oral cancer in people with low level of education (odds ratios: 1.85 ~ 5.3) and lower income patients (odds ratios: 1.7 ~ 2.41) (Boing et al, 2011;Conway et al, 2008;Johnson et al, 2010;Madani et al, 2010;Swaminathan et al, 2009). Although there was a strong association between smoking/alcohol consumption and socioeconomic status, individuals with lower education level, lower income, lower occupational status/social class, and those performing manual labor still had a higher risk of contracting head and neck cancer including oral cancer after adjusting for smoking and alcohol consumption (Boing et al, 2011;Conway et al, 2008).…”
Section: Socio-economic Factorsmentioning
confidence: 99%